Analisa Perbandingan Biaya dan Mutu Beton Menggunakan Serbuk Cangkang Telur untuk Mereduksi Pemakaian Semen - Sinay, James Boy; Sahusilawane, Tonny; Tuanakotta, Abraham (Green Publisher Indonesia, 2024)
Concrete is a very important construction material in construction so that the use of concrete is widely used. In the use of conventional concrete, there are many problems that arise, such as the use of so much cement that can affect the environment. In this study, the use of eggshell powder will be used to reduce the amount of cement in the proportion of the concrete constituent mixture as well as in the use of powder and can reduce the cost of using cement which is relatively expensive. In addition, chicken egg shell waste contains calcium carbonate where it is known that one of the constituent ingredients of Portland Cement (SP) is calcium carbonate. This study uses SNI 03-2834-2000, to calculate the proportion of the concrete mixture. Testing the compressive strength of this concrete using cylindrical specimens with a diameter of 150 mm (0.15 m) and a height of 300 mm (0.30 m) as many as 15 samples with the amount of chicken egg shell powder used at 0%, 1%, 2%, 3% and 4%. From the results of testing the average compressive strength at the age of 7 days and then converted to the age of 28 days, the average compressive strength at 0% eggshell percentage is 25.76 MPa, 1% is 22.80 MPa, 2% is 20.43 MPA, 3% is 20.13 MPa, 4% is 19.98 MPa. The greater the percentage of chicken egg shell powder, the compressive strength of the concrete decreases. For the cost of 0% concrete mix is Rp. 11,414.5, 1% is Rp. 11,342.5, 2% is Rp. 11,270.5 3% is, Rp. 11,198.5, 4% is Rp. 11,150.5 the cost of concrete using egg shell powder relatively cheaper.